ANALISIS CRITICAL PATH METHOD PROYEK PENINGKATAN JALAN JANTHO–BATAS ACEH JAYA - Mustafi, Hidayat; Zulfikar, Zulfikar; Munardy, Munardy (Pusat Penelitian dan Pengabdian Masyarakat (P2M), 2022)
ABSTRACTA construction company has limited resources in carrying out a project activity. Due to these limitations, a good and thorough planning is needed in project implementation so that existing resources can be used efficiently. To achieve this goal, the contractor and project owner have a project implementation schedule that can control the implementation of the project itself. In the Proyek Peningkatan Jalan Jantho – Batas Aceh Project, scheduling is done using the S curve method with a total implementation time of 618 calendar days or 103 weeks. In this study, the author wants to create a new scheduling scenario using the CPM (Critical Path Method) which aims to determine the work that is included in the critical path and to compare the duration of the project plan with the duration using the CPM. CPM method data analysis is done by making WBS (Work Breakdown Structure) and network diagrams using Microsoft Project. After the analysis, it was found that the work included in the critical path of Proyek Peningkatan Jalan Jantho – Batas Aceh Jaya project, namely work with the code A1 – D1 – D2 – D3 – D4 – D5 – D6 – D7 – D8 – E5 – E6 – E7 – F2 – F3 – F4 – F5 – F6 – F7 – F8 – G3 – I9 – I10 – I11 – I12 – I13 – I14 – I15 – K9 – K10 – K11 – K12 – K13 – K14 – K15 – J9 – J10 – J11 – J12 – J13 – J14 – J15 – L9 – L10 – L11 – L12 – L13 – L14 – L15 – M9 – P9 – P10 – P11 – P12 – P13 – P14 – P15 – N1 – O1 – O2 – O3 – O4 – O5 – O6 – O7 – O8 – R1 – R2 – R3 – R4 – R5 – R6 – R7 – R8 – A3 with a total duration of implementation of 615 days and the comparison of the duration between the project plan schedule using the S curve with the CPM scheduling method is 3 days. Keywords: Critical Path, CPM, WBS